Estimation of the local heat transfer coefficient in coiled tubes: Comparison between Tikhonov regularization method and Gaussian filtering technique. Issue 3 (6th March 2017) - Bozzoli, Fabio; Cattani, Luca; Rainieri, Sara; Bazán, Fermín S.V.; Borges, Leonardo S.
Abstract : Purpose: Most of the passive techniques for enhancing heat transfer inside pipes (e.g. rough surfaces, swirl-flow devices and coiled tubes) give origin to an irregular distribution of the heat transfer coefficient at the fluid–wall interface along the wall perimeter. This irregular distribution could be critical in some industrial applications, but most of the available research papers, mainly due to the practical difficulty of local measuring heat flux on the internal wall surface of a pipe, present the results only in terms of Nusselt number averaged along the wall circumference. This paper aims to study the application of inverse problem solution techniques, which could overcome this limitation. Design/methodology/approach: With regard to the estimation of the local convective heat transfer coefficient in coiled tubes, two different inverse heat conduction problem solution techniques were considered and compared both by synthetic and experimental data. Findings: The paper shows the success of two inverse problem solution techniques in the estimation of the local convective heat transfer coefficient in coiled tubes. Originality/value: This paper fulfills an identified need because most of the available research papers present the results only in terms of average thermal performance, neglecting local behavior.